Improving growth rate of Bali cattle grazing native pasture in the wet season by supplementing high quality forages - Marthen L. Mullik; Bambang Permana (Indonesian Center for Animal Research and Development (ICARD), 2009)
This grazing experiment aimed at assessing effects of providing high quality forage as supplements for Bali cattle grazing native pasture in the wet season. Twenty four Bali heifers with a mean live weight of 85.4±3.8 kg were allotted into four reatments. The treatments were (1) grazing only, (2) grazing + Gliricidia sepium leaf, (3) grazing + Acacia villosa leaf, and (4) grazing + Lannea grandis leaf. The heifers grazed together on a 25 ha Bothriochloa timorensis dominant pasture during the day (0700 h to 1700 h) in wet season, and supplements were provided at night. The supplements were given in accordance to achieve 30% refusal. Total intake was estimated by marker technique (Cr2O3). Live weight was recorded twice a month. Data were subjected to statistical analysis based on general linear model suited to a completely random design. The results showed that growth rate of Bali heifers grazing native pasture during wet season in Timor was low (35 g/d), and providing high quality forages as supplements at night significantly improved LWG by up 205%. Yet, the magnitude of LWG response varies according to type of forage, with the best result achieved by heifers given Gliricidia sepium leaf. Key Words: Bali Cattle, Grazing, Native Pasture, Wet Season, Supplement